2006
DOI: 10.21608/jvmr.2006.77922
|View full text |Cite
|
Sign up to set email alerts
|

Toxo-pathological effects induced by urea in broiler chicks

Abstract: Sixty, day-old, chicks were reared up to 3 weeks of age and then randomly divided into 4 equal groups (3 treated and one control group). Urea (46 % nitrogen) was added to the grower-finisher ration of the treated birds at levels of 1% , 3% and 5% (groups I, II & III respectively). Feed and water were available ad libitum for all birds over the time of experiment. At days 7, 20 and 30 post exposure, 5 birds from each group were weighed, bled and sacrificed. All birds spontaneously died during the experiment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
5
2
0
Order By: Relevance
“…There were cartilaginous and osseous nodules among the pulmonary tissue. These microscopic findings completely agreed with Abdou et al (2006); Elkhawaga (1999) who reported similar lesions in chicks. Moreover, the lung showed emphysema and air alveoli of the lung tissue showed focal epithelization of the lining epithelium with dilatation and desquamation of the epithelial layer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There were cartilaginous and osseous nodules among the pulmonary tissue. These microscopic findings completely agreed with Abdou et al (2006); Elkhawaga (1999) who reported similar lesions in chicks. Moreover, the lung showed emphysema and air alveoli of the lung tissue showed focal epithelization of the lining epithelium with dilatation and desquamation of the epithelial layer.…”
Section: Discussionsupporting
confidence: 91%
“…Urea has been used as a cheap protein substitute in the poultry feed (Pervaz et al, 1993). However, toxicity can occur when chicks are kept on urea treated feed (Jabbar, 1994;Pervaz, 1994;Abdou et al, 2006). Recently, commercial pet food was adulterated with melamine (Brown et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The decreased FI and BWG of broiler chicks fed the urea-containing diets in the present study is in harmony with the results of Pervaz et al (1994, Javed et al (1995, Abdou et al (2006) and Islam et al (2006) who reported significant reductions in growth performance of broiler chicks fed diets containing between 2 to 6% urea. However, Das (1997) observed no adverse effects of feeding urea up to a concentration of 15 g/kg in the diets on the growth of chicks.…”
Section: Growth Performance Of Chickssupporting
confidence: 93%
“…**: Significant at P≤0.01. The increase in blood urea level of broilers due to feeding ureacontaining diets, observed herein, has also been reported by several investigators (Bruckental and Nitsan, 1981;Karasawa and Umemoto (1993;Nagalakshmi et al, 1999;Abdou et al, 2006;Al-Ankari, 2006;Islam et al, 2006). Similar observations were reported when urea, as a NPN source, was included in rabbit (Ismail et al, 1999) and swine (Kornegay et al, 1970) diets.…”
Section: Blood Parameters Of Broiler Chickssupporting
confidence: 88%
See 1 more Smart Citation